1985
DOI: 10.1037/0033-2909.98.3.538
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent contraceptive behavior: A review.

Abstract: This review examines the psychologically oriented literature on adolescent contraceptive use. Descriptive studies, individual difference studies, and theory-based studies from family planning, medical, and applied journals are covered, as well as studies appearing in psychology journals. The research covered suggests that adolescents are largely uninformed about reproductive physiology and about many methods of contraception. They have negative attitudes toward contraception generally and toward using contrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
6

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(91 citation statements)
references
References 105 publications
(388 reference statements)
1
84
0
6
Order By: Relevance
“…This is an important point, because adolescents are notorious for not using contraception. 40 If the respondents were not really engaged in contraceptive decision making (as, for example, the teen clients of a family-planning clinic would be), but were role playing at the behest of the researchers, then the behavioral intentions questions become problematic, as they must be answered from a real-life perspective.…”
Section: Role Playingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important point, because adolescents are notorious for not using contraception. 40 If the respondents were not really engaged in contraceptive decision making (as, for example, the teen clients of a family-planning clinic would be), but were role playing at the behest of the researchers, then the behavioral intentions questions become problematic, as they must be answered from a real-life perspective.…”
Section: Role Playingmentioning
confidence: 99%
“…In fact, several surveys have indicated that a major reason for the nonuse of contraception among adolescents is that intercourse was unexpected. 40 It is difficult to plan ahead for unanticipated events. Researchers must be very careful not to assume decision making or planning where it may not exist.42…”
Section: Situational Constraintsmentioning
confidence: 99%
“…Over 60% of contraception users switch methods at some time point, and many discontinue a method within the first three months of use [6][7][8][9]. Variable patterns of OCP pill-taking during periods of transition into and out of OCP use may make these especially vulnerable times in terms of method adherence [10]. Condom use during transition periods is especially important for contraceptive as well as STI prevention purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Reglas y sanciones a las violaciones de las normas familiares, supervisión por otros 17,18 como mejor nivel educacional del padre [20][21][22][23] , edad materna, número de hermanos, fueron asociados a la sobrevida del uso de anticonceptivos. Sin embargo, otras variables como filiación, figura de crianza, composición familiar y actividad de los padres, no mostró asociación, lo I N V E S T I G A C I Ó N cual es consistente con lo encontrado en otros estudios 17,[19][20][21][22] .…”
Section: Discussionunclassified
“…¿Es que los padres más educados tienden a conversar más abiertamente de anticonceptivos con sus hijos y a apoyar más el uso de anticonceptivos de adolescentes? [20][21][22][23] . No hay estudios que demuestren que variables familiares como composición familiar y tamaño de la familia, nivel socioeconómico, esté relacionada directamente al uso de anticonceptivos en adolescentes 17,[19][20][21][22] .…”
Section: N V E S T I G a C I ó Nunclassified